Micro-CT Evaluation of Gutta-Percha Removal by Two Retreatment Systems - Rubino, Gustavo Alberto; de Miranda Candeiro, George TÃ¡ccio; Iglecias, Elaine Faga; Lemos, Ã‰rico de Mello; Caldeira, Celso Luiz; Gavini, Giulio (Iranian Endodontic Journal, 2018)
Introduction: The aim of the present ex vivo research was to compare the remaining filling material and the volumes of dentine removed after retreatment of curved canals with two rotary systems naming ProTaper Universal Retreatment and Mani NRT-GPR using micro-computed tomography (micro-CT). Material and Methods: Forty mandibular molars containing two completely separated canals, with curvature angle of 25-35° and a curvature radius <10 mm were prepared to the Mtwo instrument 35/0.04 and filled with warm gutta-percha and AH-Plus sealer. The teeth were randomly divided into 2 groups (n=20), according to the retreatment system evaluated: ProTaper Universal Retreatment (PR group) or Mani NRT-GPR (MR group). Retreatment was considered complete when the working length was reached and when smooth dentinal walls were observed, with no evidence of filling material adhered to instruments or in the irrigating solution. Preoperative and postoperative micro-CT images were obtained with an isotropic voxel size of 11.88 µm to observe the volume of residual filling material in the canals and dentine removed after retreatment. Statistical analysis was performed by Student’s t-test (P<0.05). Results: The mean percentage of remaining filling material was 12.96% for PR group and 24.26% for MR group (P=0.0056). The percentage of dentin removal was greater in the PR group (5.02%) than MR group (1.36%) (P=0.0028). Both systems failed to completely remove the filling material from the canals. Conclusion: ProTaper Universal Retreatment system was more effective than Mani NRT-GPR system regarding removal of root filling material and also removed significantly more dentine after retreatment of curved mesial root canals of mandibular molars. Keywords: Dental Instruments; Endodontics; Gutta-Percha; Endodontic Retreatment